Economic Reform and Structural Adjustment in East European Industry - Borensztein, Eduardo (IMF Working Papers; Working Paper ;, 1994)
A consistent set of disaggregated industrial output data for four Eastern European countries is examined In order to determine the extent to which structural adjustment has taken place since the initiation of market-oriented reform. The latter created a massive relative price shock whose affects on the structure of the industrial sectors of these economies is shown to have been relatively small, at least one to two years after the reforms. An implication is that one argument in favor of more gradualist reform-based on the premise that more gradualism implies a smaller output cost in the short run-is questionable. By and large in these economies, the output cost associated with the removal of relative price distortions may still have to be faced.